Fermentation of bladderwrack (Fucus vesiculosus) and its impact on composition - Oyedokun, Temitope (My University, 2024)
In response to consumers demand for non-dairy products due to lactose intolerance and the growing preference of a vegan diet, production of plant-based fermented products such as kimchi, sauerkraut have increased. The majority of plant-based fermented products utilise terrestrial vegetables as their substrate as seen in the use of lactic acid fermentation in the processing of cucumber, cabbage and olives. However, research on the fermentation of aquatic plants such as seaweeds remains limited. Bladderwrack (F. vesiculosus), known and utilised for its distinctive saltiness (high iodine concentration) and richness in bioactive compounds is a small-sized brown seaweed. Its non-volatile compounds have been studied for their potential value in different industrial applications. However, a detailed identification of its volatile compounds is essential in defining desirable aroma and flavours to be enhanced during processing to meet consumer preferences. The aim of this study was to investigate changes in the chemical composition (pH, organic acids, and volatiles) of fermented bladderwrack. In this study, fresh bladderwrack was processed at different conditions (blended and chopped) and treatments (raw, heat treatment and enzymatic hydrolysis) to prepare seaweed broth for fermentation. The seaweed broth was fermented with cells of L. plantarum strains for 120 h at 37 C. In monitoring the process, pH was measured every 24 h. Organic acids were analysed with gas chromatography coupled with flame ionization detector after sialylation and the profile of volatile compounds in the fermented seaweeds was investigated using headspace solid-phase microextraction with gas chromatography–mass spectrometry. A decrease in pH was observed in heat treated samples compared to the raw samples. Lactic acid and malic acid were present in some fermented samples. The volatile analysis identified thirty-eight compounds in both raw and fermented samples. Among these were identified two aldehydes, two benzenes, three acids, four esters, five hydrocarbons, seven ketones, and ten alcohols. Bladderwrack’s complex polysaccharides composition presents intrinsic challenges for a successful fermentation, yet it remains a viable means for the development of innovative seaweed products. Nonetheless, additional research is necessary to optimise the process. This involves exploring different starter cultures, alternative seaweed pre-treatments and enhancers to promote the fermentation process of bladderwrack for potential food use.
Keywords: bladderwrack, fermentation, lactic acid bacteria, volatiles, GC-MS